Evaluation of menopausal disorders in women with different levels of bone mineral density - I S Zakharov (IP Berlin A.V., 2015)
The publication presents an assessment of the severity of menopausal disorders in women with different levels of bone mineral density (BMD). The study included 96 women in early postmenopausal women who underwent dual-energy X-ray absorptiometry. Evaluation of menopausal disorders was carried out on the basis of international menopausal scale. Based on the work conducted by an association between BMD of lumbar vertebrae and overall assessment of menopausal disorders. Also there was a correlation with markers of oxidative stress level of the BMD and the severity of menopausal syndrome.